Penyebaran Informasi dalam Upaya Memutuskan Penularan Covid 19 di Wilayah Harapan Baru Bekasi - Navanti, Dovina; Lestari, Tyastuti Sri; Solihin; Montororing, Yuri Delano Regent; Panday, Rorim (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
This Community Service Program is carried out with the aim of providing information related to the transmission and prevention of the Covid 19 virus. The main target of this Community Service program is the community or local residents who often visit the Duta Harapan Housing lake, North Bekasi. With the consideration that the majority of people often do activities around the Duta Harapan lake, such as selling and recreation. Public awareness of the Covid-19 pandemic is very lacking, many people ignore Covid-19. Thus it is necessary to make efforts to increase public awareness about preventing the transmission of Covid-19, to help public awareness to provide insight or information to the public regarding several things in handling and preventing the deployment of the COVID- 19 Virus in New Normal life. With the number of positive patients exposed to this virus which is increasing, the community does not stop worrying and there are new policies from the government. From the results of the interview, it can be seen that the public does not know much information about Covid-19. So the solution we are doing is to provide information directly to the community. With the Community Service program through the dissemination of information, with the target of the community being able to create increased information and public understanding about Covid-19, a movement strategy is created to prevent and anticipate the deployment of Covid-19 in the local area, and the creation of information media that can be a guide for the community in dealing with the deployment of the corona virus, and continue to apply health protocols even though there is a decrease in the level of spread until the government gives instructions in the next stage of life.